I stay near you : 1 story in 3 - Kerr, M. E. (New York, N.Y. : Harper & Row, 1985)
Three generations suffer the consequences of an ill-fated romance between a sixteen-year-old from the wrong side of the tracks and the son of the richest man in a small upstate New York town.
I stay near you -- Welcome to my disappearance -- Something I've never told you.
"A Charlotte Zolotow book.".
For ages 12 up.
Horn Book.
Notable/Best Books (A.L.A.).
Wilson's Senior High School.
5.5